Moroccan and Guatemalan military servicemen: the role of war and genocide propaganda - Esparza, Marcia (Southernising criminology, 2024)
Based on multi-country fieldwork with Indigenous communities, military records, and museums, this chapter offers an interdisciplinary analysis – decolonial criminology, critical military studies, war, and genocide – of the Guatemalan and Spanish military to understand the racialized hierarchies of the relationship between the colonizer and the colonized. These hierarchies differentiate between the ‘good Indians’ and the ‘bad Indians’. In both cases during war situations, right-wing, fascist armies have reabsorbed the colonized, as colonial soldiers, into their ranks because they are needed to carry out deadly military campaigns. Specifically, I focus on the persuasive role that military war propaganda plays in co-opting Indigenous troops’ support to fight wars for the colonizer. What where they told by the military to get them to serve in counterinsurgency, they had little to gain from? Should critical Southernizing criminology turn its gaze to an examination of colonial and Cold War military crimes?